2013
DOI: 10.1289/ehp.1306734
|View full text |Cite
|
Sign up to set email alerts
|

Perinatally Administered Bisphenol A as a Potential Mammary Gland Carcinogen in Rats

Abstract: Background: Environmental exposure to bisphenol A (BPA) affects mammary gland development in rodents and primates. Prenatal exposure to environmentally relevant doses of BPA increased the number of intraductal hyperplasias and ductal carcinomas in situ by 50 days of age in Wistar-Furth rats.Objective: We aimed to determine whether BPA exposure of dams during gestation only or throughout lactation affects the incidence of mammary gland neoplasia in female offspring.Methods: We treated pregnant Sprague-Dawley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 51 publications
3
102
0
2
Order By: Relevance
“…[137][138][139] Another recent study revealed the presence of carcinomas in the mammary glands of rats exposed to low doses of BPA only during early development in the absence of any additional carcinogen treatment, providing further evidence that the mammary gland is affected by BPA. 140 A recent weight-ofevidence analysis found strong support for low dose effects and high levels of consistency between studies for both endpoints; 5 low doses were found to alter mammary gland morphology at many life stages, and numerous studies reported that low doses increase the incidence of preneoplastic and neoplastic lesions, as well as increase the response to chemical carcinogens. Some of these studies are discussed in more detail below.…”
Section: -53mentioning
confidence: 99%
“…[137][138][139] Another recent study revealed the presence of carcinomas in the mammary glands of rats exposed to low doses of BPA only during early development in the absence of any additional carcinogen treatment, providing further evidence that the mammary gland is affected by BPA. 140 A recent weight-ofevidence analysis found strong support for low dose effects and high levels of consistency between studies for both endpoints; 5 low doses were found to alter mammary gland morphology at many life stages, and numerous studies reported that low doses increase the incidence of preneoplastic and neoplastic lesions, as well as increase the response to chemical carcinogens. Some of these studies are discussed in more detail below.…”
Section: -53mentioning
confidence: 99%
“…Thus, these preliminary studies suggest that low‐dose BPA has the potential to pose health hazards. Recent studies have also aimed to evaluate the role of BPA in carcinogenesis,7, 22, 23 and have indicated that exposure to BPA may account, at least partially, for the increased incidence of multiple cancers, including breast cancer,24, 25, 26, 27 ovarian cancer,28, 29 uterine cancer,30 prostate cancer,31, 32 testicular cancer,33 and liver cancer 34. The carcinogenic effects of BPA are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, even in ϯ low concentration (ng/L), BPA has been reported to cause adverse environmental and health effects because it can pose potential estrogenic and toxicological risk [9,10]. It was also reported that BPA has been associated with metabolic disorders including obesity and diabetes [11], and an increasing risk of miscarriages and cardiovascular disease in humans, and potential mammary gland carcinogen in mice [12]. Therefore, it is urgent to develop an efficient method to remove BPA in low concentration from aquatic environment.…”
Section: Introductionmentioning
confidence: 99%